Effect of Super-Particle Weight Factor on Particle-in-Cell Simulations in Low Pressure Capacitively Coupled Plasmas - Stewart, M. C.; Wen, D.-Q.; Verboncoeur, J. (IEEE conference record-abstracts - IEEE International Conference on Plasma Science, 2023)
Fully kinetic Particle-in-Cell/Monte Carlo Collisions (PIC/MCC) is an essential tool in understanding the complex physics of plasmas (CPP). Numerical accuracy and stability are important for PIC/MCC simulations and have been the subject of studies since PIC/MCC' S concepetion. Recent work reported that the plasma density of explicit electrostatic PIC/MCC simulations at steady state does not converge while decreasing the super-particle weight for low-pressure CPPs [1]. The simulations in [2] suggest around a thousand super-particles per cell is required for convergence, suggesting a high computational cost, especially in 2D or 3D cases. In this work, we revisited the super-particle weight issue and explored the dependence of the plasma discharge properties on the super-particle weight. We will explore the numerical effects and physics regime related to this issue.